2011
DOI: 10.1111/j.1439-0329.2010.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic speciation in Hymenoscyphus albidus

Abstract: Ash dieback caused by the mitosporic ascomycete Chalara fraxinea is a novel disease of major concern affecting Fraxinus excelsior and Fraxinus angustifolia in large parts of Europe. Recently, its teleomorph was detected and assigned to Hymenoscyphus albidus, which has been known from Europe since 1851. In this study, we present molecular evidence for the existence of two morphologically very similar taxa, H. albidus, which is lectotypified and Hymenoscyphus pseudoalbidus sp. nov. Differences were found between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
273
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(289 citation statements)
references
References 36 publications
8
273
1
6
Order By: Relevance
“…The taxonomy of R. subterranea was recently revised based on both morphological and rDNA data (Kirchmair et al 2008 (Queloz et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The taxonomy of R. subterranea was recently revised based on both morphological and rDNA data (Kirchmair et al 2008 (Queloz et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Its teleomorph, based on morphological features, was initially designated as Hymenoscyphus albidus (Kowalski and Holdenrieder 2009a). Further research based on DNA sequences of isolates from Switzerland and other European countries revealed that H. albidus represents an aggregate of two clearly delimited species (Queloz et al 2011). One was related to the non-pathogenic H. albidus sensu stricto, which had been known in Europe since 1850 (Kowalski and Holdenrieder 2009a;Baral and Bemmann 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The second was described as a new cryptic species, Hymenoscyphus pseudoalbidus, with Ch. fraxinea as its anamorph (Queloz et al 2011). A new taxonomic designation was made by , who stated that under the rules for the naming of fungi with pleomorphic life cycles, adopted in July 2011 (Hawksworth 2014), the nomenclaturally correct name for the fungus causing the current ash dieback in Europe is Hymenoscyphus fraxineus with the basionym Chalara fraxinea, and Hymenoscyphus pseudoalbidus as a taxonomic synonym of H. fraxineus.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the fungus Hymenoscyphus pseudoalbidus (Helotiales, Ascomycota) was proven to be the causal agent of ash dieback (Queloz et al, 2011, Zhao et al, 2012, a disease that has rapidly spread across Europe in the course of the last 20 years. This notorious pathogen can only be found in ash trees (Fraxinus) and is responsible for severe dieback of the European ash (Fraxinus excelsior).…”
Section: Introductionmentioning
confidence: 99%